2016
DOI: 10.2136/sssaj2015.07.0262
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Rice Grain Zinc through Zinc Fertilization and Water Management

Abstract: Core Ideas Rice grain‐Zn concentration increased with more aerobic soil conditions. Fertilizer‐Zn applied to soil had limited effect on rice grain‐Zn concentration. Rice paddy water management affected soil redox potential and DTPA‐extractable Zn. Combined water and Zn management are useful for agronomic Zn biofortification. Agronomic biofortification was not sufficient to meet rice Zn nutrition targets. Increasing rice (Oryza sativa) grain‐Zn concentration is important for achieving improved human nutrition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
1
27
2
1
Order By: Relevance
“…3), suggesting the beneficial effect of LSD on grain Zn loading for genotype IR69428. Our results slightly differ from those of Tuyogon et al 10,. who reported that AWD had a positive effect on grain Zn concentration but that the contributed increase was minimal (2.0 μg g −1 ); hence, the desired grain Zn concentration (30.0 μg g −1 ) was not achieved.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…3), suggesting the beneficial effect of LSD on grain Zn loading for genotype IR69428. Our results slightly differ from those of Tuyogon et al 10,. who reported that AWD had a positive effect on grain Zn concentration but that the contributed increase was minimal (2.0 μg g −1 ); hence, the desired grain Zn concentration (30.0 μg g −1 ) was not achieved.…”
Section: Discussioncontrasting
confidence: 99%
“…The concentrations of DTPA-extractable Zn under MSD in our pot experiments (0–2 cm soil depth) were up to 8 times higher than the values reported by Tuyogon et al 10. for field experiments at 0–2 cm soil depth under AWD and ZF at 10 kg Zn ha −1 .…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations